PENGARUH LITERASI KEUANGAN, PENGGUNAAN DIGITAL PAYMENT DAN SELF CONTROL TERHADAP PERILAKU KONSUMTIF MAHASISWA FAKULTAS EKONOMI UNIVERSITAS BOYOLALI (Studi Kasus pada Mahasiswa Fakultas Ekonomi Angkatan 2019 Sampai 2023) - Azizah, Anggie Sintia; Susana Theorupu, Milka; Referli, Andria; Rachman, Arif Nugroho (Universitas Boyolali, 2025)
ABSTRACT This research aims to determine the influence of financial literacy, use of digital payments and self-control on the consumptive behavior of students at the Faculty of Economics Boyolali University. The research method used was quantitative by collecting data through questionnaires distributed to 112 respondents. Data analysis was carried out using SPSS version 26. The results of the hypothesis test or t test show that financial literacy, use of digital payments and self control have a significant influence on the consumptive behavior variable, namely 0.001 < 0.05 for the variable X1, 0.000 < 0 respectively. .05 for variable X2 and for variable X3 it is 0.000 < 0.05. The simultaneous test shows that the three independent variables together have a significant influence on the dependent variable, namely consumer behavior. The coefficient of determination shows 0.768. If calculated using the determination formula, the result obtained is 0.768 x 100% = 76.8%. that the independent variable is able to explain around 76.8% of the variability in consumer behavior of students at the Faculty of Economics, Boyolali University. This study provides important insights for students at the Faculty of Economics, Boyolali University regarding financial literacy, digital payments, self-control and consumer behavior.